LIVE: Lightweight Integrity Verification for Named Data Networking (International Journal of Engineering and Computer Science, 2017)
Named information organizing (NDN) is another worldview for the future Internet wherein hobby and information parcels convey content names as opposed to the present IP worldview of source and destination addresses. Security is incorporated with NDN by installing open token mark in every information bundle to empower check of credibility and uprightness of the substance. Be that as it may, existing heavyweight signature and check calculations to avoid all inclusive uprightness confirmation among NDN nodes, which may bring about substance contamination and refusal of administration assaults. We propose a lightweight respectability confirmation (LIVE) engineering, an expansion to the NDN convention, to address these two issues. Besides, it permits a substance supplier to control content access in NDN hubs by specifically dispersing uprightness check tokens to approved hubs. We also introduce IP address verification to avoid unauthorized users. Here our tokens valid from the user can access his accounts from another system.